Simulated patient-based teaching of medical students improves pre-anaesthetic assessment: A rater-blinded randomised controlled trial. Issue 5 (May 2020) - Berger-Estilita, Joana M.; Greif, Robert; Berendonk, Christoph; Stricker, Daniel; Schnabel, Kai P.
Abstract : BACKGROUND: Pre-anaesthetic assessment of patients is a complex competency that needs to be taught during anaesthesia clerkships. OBJECTIVES: We aimed to improve student teaching and investigated the effectiveness of trained 'simulated patients' (lay persons or actors trained to portray specific roles or symptoms) in the teaching of medical students to perform routine pre-anaesthetic assessments. We hypothesised that the intervention of one 30-min teaching sequence with a simulated patient will improve the performance of year 4 medical students in pre-anaesthesia assessment of elective surgical patients, compared with the control of standard apprentice-based teaching. DESIGN: Randomised controlled trial. SETTING/PARTICIPANTS: One hundred and forty-four year 4 medical students at the University of Bern. INTERVENTION: These students were randomised to either the standard clinician-supervised learning in the operating theatre ( n =71; control group) or a single teaching session with a simulated patient (nonhealthcare provider, as a trained layperson) ( n =73; intervention group). Both groups of students then performed pre-anaesthetic patient visits. The student performances during these visits were assessed according to the mini-Clinical Evaluation Exercise tool by trained anaesthesiologists blinded to randomisation. The 71 students in the standard clinical supervision group also underwent the simulated patient teaching session on the day following the assessments. RESULTS: The students in the intervention group of simulated patient teaching scored significantly higher in both their mini-Clinical Evaluation Exercise overall impression scores (8.8 ± 0.8 vs. 8.3 ± 0.9; P  = 0.004) and mean domain scores (8.7 ± 0.8 vs. 8.3 ± 0.9; P  = 0.01), compared with those of the control group with the standard clinical supervision. CONCLUSION: The current single teaching encounter with a trained layperson acting as a simulated patient improved medical student performances in their pre-anaesthetic clinical assessment of surgical patients. This might be a suitable alternative to reduce the teaching burden for busy and costly clinicians. Abstract : Supplemental Digital Content is available in the text